2021
DOI: 10.1140/epja/s10050-021-00376-0
|View full text |Cite
|
Sign up to set email alerts
|

The Hussein–McVoy formula for inclusive breakup revisited

Abstract: In 1985, Hussein and McVoy [Nuc. Phys. A445 (1985) 124] elucidated a formula for the evaluation of the nonelastic breakup ("stripping") contribution in inclusive breakup reactions. The formula, based on the spectator core model, acquires a particularly simple and appealing form in the eikonal limit, to the extent that it has become the standard procedure to analyze single-nucleon knockout reactions at intermediate energies. In this contribution, a critical assessment of this formula is presented and its conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…[22]). It has been shown that the integrated cross sections produced in such models agree with those from the eikonal model, proving that this aspect does not have a strong impact on the extracted SFs [24]. The second approximation, the core-spectator approximation, assumes that the core degrees of freedom are "frozen" during the collision process.…”
Section: +Y (Y )mentioning
confidence: 99%
See 1 more Smart Citation
“…[22]). It has been shown that the integrated cross sections produced in such models agree with those from the eikonal model, proving that this aspect does not have a strong impact on the extracted SFs [24]. The second approximation, the core-spectator approximation, assumes that the core degrees of freedom are "frozen" during the collision process.…”
Section: +Y (Y )mentioning
confidence: 99%
“…[16][17][18][19][20][21] discuss the importance of short-and long-range correlations for structure predictions and Refs. [22][23][24][25][26][27] address the validity of the eikonal approximation. Similarly many studies have been done testing the validity of the theories used in the transfer analyses [28][29][30][31], including benchmarks of the reaction models.…”
mentioning
confidence: 99%
“…Since the wavefunction (38) takes into account breakup effects [38], the eikonal approximation is able to describe physical process in which the hole or nucleon absorption takes place before as well as after (or simultaneously to) the breakup process. However, it should only be applied when the kinematical conditions are suitable for an eikonal approximation, i.e., when the bombarding energy is large enough.…”
Section: B Eikonal Approximationmentioning
confidence: 99%